2000
DOI: 10.1123/jsr.9.4.304
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rehabilitation Methods in the Treatment of Patellar Tendinitis

Abstract: Objective:To compare outcomes of 2 rehabilitation protocols on patellar tendinitis subjects.Design:Prospective, randomized, blinded, controlled clinical trial.Setting:Outpatient rehabilitation clinic.Subjects:Randomized into 2 rehabilitation groups—traditional (n= 10) and ASTM AdvantEDGE (n= 10).Main Outcome Measures:Clinical data and self-reported questionnaires collected at 0, 6, and 12 weeks.Results:On completion of the 6th week, 100% of the ASTM AdvantEDGE group and 60% of the traditional group had resolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 24 publications
0
49
0
Order By: Relevance
“…10 Preliminary animal model studies comparing the effects of IASTM-treated, with contralateral untreated injured, soft tissue structures have shown increased fibroblast recruitment and activation in injured tendon 11,12 and improved biomechanical, histological, and vascular properties in the healing ligament. 13,14 Case reports and pilot studies using IASTM have also demonstrated promising outcomes for diagnoses such as patellar tendinopathy, 15 chronic ankle pain, 16 plantar fasciitis, 17 post-natal calf pain, 18 knee pain, 19 carpal tunnel syndrome, 20 cumulative trauma disorders, 21 and lateral epicondylitis/epicondylosis. [22][23][24] Currently, there are no known clinical studies on the use of IASTM for any conditions affecting the finger in an instrumentalist.…”
Section: Introductionmentioning
confidence: 99%
“…10 Preliminary animal model studies comparing the effects of IASTM-treated, with contralateral untreated injured, soft tissue structures have shown increased fibroblast recruitment and activation in injured tendon 11,12 and improved biomechanical, histological, and vascular properties in the healing ligament. 13,14 Case reports and pilot studies using IASTM have also demonstrated promising outcomes for diagnoses such as patellar tendinopathy, 15 chronic ankle pain, 16 plantar fasciitis, 17 post-natal calf pain, 18 knee pain, 19 carpal tunnel syndrome, 20 cumulative trauma disorders, 21 and lateral epicondylitis/epicondylosis. [22][23][24] Currently, there are no known clinical studies on the use of IASTM for any conditions affecting the finger in an instrumentalist.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of ASTM in rats 6,17 have indicated an increase in fibroblast recruitment and healing in chemically induced tendinitis. In the treatment for patellar tendinitis, 69 after 6 weeks of using ASTM, 100% of pain and functional impairment resolved. In contrast, symptoms in the traditional therapy group (not using ASTM) resolved by only 60%.…”
Section: Exercise and Therapeutic Exercisementioning
confidence: 99%
“…The objective is therefore to regain or improve strength, ROM, and endurance. 66 To assist with ROM, Cyriax massage, augmented soft-tissue mobilization (ASTM), 16,17,68,69 and active ROM are included. Studies of ASTM in rats 6,17 have indicated an increase in fibroblast recruitment and healing in chemically induced tendinitis.…”
Section: Exercise and Therapeutic Exercisementioning
confidence: 99%
“…One study 13 compared treatment of patellar tendinopathy with a massage device with those treated traditionally (stretching, frictions, electrophysical modalities). The main outcome measure used in this study was a scale designed to evaluate long term changes in the patellofemoral joint, 14 which may lack sensitivity to symptoms and functional changes in patellar tendinopathy.…”
Section: Massage/frictionsmentioning
confidence: 99%
“…Authors used unvalidated 16 or adapted knee pain scales, 12 scales not specifically designed for tendinopathy, 13 or generic tendon scales 30 31 that are not necessarily appropriate or specific for the patellar tendon. The outcome scale used in both conservative and surgical papers (excellent, good, fair, poor) 32 lacks specificity and sensitivity in quantifying outcome after treatment for patellar tendinopathy.…”
Section: Outcome Measuresmentioning
confidence: 99%